2022
DOI: 10.1016/j.ijdrr.2021.102723
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of community satisfaction with the government's COVID-19 pandemic response in Aceh, Indonesia

Abstract: Countries around the world are still struggling due to the COVID-19 pandemic. No exception with Indonesia, a developing country with the highest mortality rate and the lowest number of tests in Asia. Located in the northernmost, Aceh is one of the poorest provinces with a history of long-term conflict is not in the best condition to face a pandemic. This study's objective is to assess the local government's performance in responding to this pandemic according to the Acehnese community's level of satisfaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
(56 reference statements)
0
16
0
3
Order By: Relevance
“…However, relatively higher than the USA (47.0%) and the UK (46.0%) [ 34 ]. Similarly, a study conducted in Indonesia reported lower satisfaction of communities with the local government's performances, which include: anticipation, early detection, containment, control and mitigation, and elimination [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, relatively higher than the USA (47.0%) and the UK (46.0%) [ 34 ]. Similarly, a study conducted in Indonesia reported lower satisfaction of communities with the local government's performances, which include: anticipation, early detection, containment, control and mitigation, and elimination [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indonesia, a country with the fourth highest population, is likely to be severely affected by the pandemic [20]. In November 2020, the death rate from COVID-19 in Indonesia was the highest in Asia (8% in 2020) [21]. On 22 December 2021, Indonesia recorded 4,261,000 total cases, 144,034 total deaths, and 15,340 total cases per million people, 519 total deaths/million of the population (https://www.worldometers.info/coronavirus/, accessed on 22 December 2021).…”
Section: Introduction 1research Backgroundmentioning
confidence: 99%
“…To identify key CEPC factors, some scholars have studied the quantitative or qualitative relationship between influencing factors and the capacity of community resilience. For example, through Grounded Theory, identifying the factors as a result of which urban residents fail to respond to the governance of the community epidemic in a timely manner and the mechanism of action between them [ 33 ], or recognizing the influencing factors (political, economic, socio-cultural, infrastructure and human health) of community epidemic recovery [ 34 ]; validating the relationship model between community awareness, community resilience and mental health through Structural Equation Modeling [ 35 ]; using the Pearson Correlation Coefficient to characterize the correlation between the number of confirmed cases of COVID-19 in Wuhan and socioeconomic factors such as community characteristics and distance variables [ 36 ]; the impact of the level of urban governance on CEPC and the mental health risk of residents is analyzed by Ordinary Least Squares [ 37 , 38 , 39 ]; using Multiple Linear Regression to analyze the main influencing factors and influence degree of community resilience during the epidemic [ 5 ]; establishing a Relative Importance Matrix to analyze the relationship between community residents’ satisfaction and local government performance during the COVID-19 epidemic [ 40 ]; using Sensitivity Analysis to evaluate the impact of key influencing factors on the epidemic contribution of disaster response capability [ 41 ].…”
Section: Research Progressmentioning
confidence: 99%